상태-공간모형을 이용한 Nelson-Siegel 이자율 기간구조 추정과 예측 - 송준혁; Joon Hyuk Song (Seonmul yeongu (Online), 2011)
본 논문에서는 Nelson-Siegel 모형의 횡단면적 제약을 완화하기 위해 시계열적 특성을 반영한 상태-공간 모형을 설정하여 수익률곡선을 추정하고 미래 수익률에 대한 예측성과를 비교해 보았다. 자료를 분석한 결과 Nelson-Siegel 요인들은 수익률곡선의 수준, 기울기 및 곡률을 잘 표현하고 있으며 수익률곡선의 변곡은 대략 55개월 근처에서 형성되어 있음이 관찰되었다. 한편 Nelson-Siegel의 개별요인들에 대한 단위근 검정 결과 이들 요인 모두 단위근이 존재하였으나 각 요인들의 차분에 대한 단위근 검정결과는 모두 안정적인 시계열로 나타나 이들 요인들은 I(l) 변수들로 판명되었다. 상태-공간 Nelson-Siegel 모형이 수익률곡선을 예측하는 데 얼마나 유용한 지를 살펴보기 위해 표본외 예측을 수행하고 이를 임의보행, Fama-Bliss 그리고 Cochrane-Piazzesi 모형과 비교한 결과 Fama-Bliss 모형의 예측력이 가장 열등한 것으로 나타났다. Nelson-Siegel 모형과 임의보행 모형의 예측성과는 예측시계에 따라 상이하게 나타났는데 단기에서는 Nelson-Siegel 모형이, 장기에서는 임의보행 모형의 예측성과가 우수한 것으로 관찰되었다. This paper estimates a Nelson-Siegel model under the state-space representation in order to circumvent the shortcomings of the conventional Nelson-Siegel model and evaluates the predictive ability of the estimated model. The results indicate that the estimated Nelson-Siegel time-varying three factors have close relations to their counterparts: level, slope and curvature and the inflection of the Korean yield curve is located around the maturity of 55-month. Meanwhile, each factor is found to have unit-root but differenced-factors do not show signs of unit-roots, hence proved I(1) series. In order to assess the efficacy of the estimated model, we compare the yield prediction from our model with several natural competitors: random walk, Fama-Bliss, and Cochrane-Piazzesi. With respect to out-of-sample performance, Fama-Bliss model proves to be the worst in term structure forecasts in Korea. The predictive performance differs between the random walk and the state-space Nelson-Siegel model depending on the forecast horizon lengths. At the shorter horizon, the state-space Nelson-Siegel model outperforms the random walk, but the table is turned in the longer horizon.